Lineament mapping using sig and optical and radar remote sensing: The case of the Tafilalet plain (Southeastern Morocco) - Mouzoun Ouafae; Iharzi Chaimae; Kassou Amina; Essahlaoui Ali; Khrabcha Abdelali (E3S Web of Conferences)
This research focuses on the mapping of lineaments in the Tafilalet plain, located in south-eastern Morocco, using a combination of optical (Landsat 8), radar (Sentinel-1A) and 10 m resolution digital terrain model (SRTM) remote sensing. Radiometric and geometric corrections, as well as directional filters, were applied to extract lineaments of the study area. These lineaments were then validated using geological and topographical maps and Google Earth Pro images. Statistical analysis of the orientations revealed six main directions: N-S, NE-SW, NW-SE, E-W, NNE-SSW, NNW-SSE, with a predominance of N-S to NE-SW orientations, corresponding to the hydrological dynamics of the region. This approach demonstrates the effectiveness of remote sensing techniques in providing precise information on geological structures, thereby facilitating understanding of the subsurface and hydrological characteristics of the area studied.